Perspectives and Challenges in Pastoral Care for Child Sex Offenders - Demasure, Karlijn (Counseling et spiritualité, 2016)
This article deals with the difficult practice of pastoral and spiritual accompaniment of people who have committed child sexual abuse. This paper identifies some particular needs and challenges presented by offenders as well as possible traps that the pastoral worker needs to avoid. It also describes some basic pastoral attitudes that are helpful in the accompaniment of sexual offenders. The complexity of caring for child sex offenders points to the need for solid formation both on the psychological and the pastoral level. Not being trained in psychology will put pastoral workers at risk of falling into the traps of cognitive distortions and a false forgiveness. Not being trained on a pastoral level might lead to a refusal to work with offenders and not being able to confront distorted God images.